(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: Describe clinical and laboratory features and evaluate the outcome of hemophagocytic lymphohistiocytosis in adults at the National Institute of Hematology and Blood Transfusion in 2018-2023. Method and patients: Describes a retrospective case series of 96 patients diagnosed with hemophagocytic lymphohistiocytosis at the National Institute of Hematology and Blood Transfusion in 2018-2023. Patients over 15 years old, were diagnosed and treated according to the diagnostic criteria of HLH 2004. Results: The study’s results showed that the patients’ age range was from 16 to 83 years old, while the average was 50 years. The incidence of this disease in males was higher than in females (male/ female is 2/1). Clinical features include fever (94.8%), splenomegaly (59.4%) and hepatomegaly (40.6%). In terms of laboratory features, the prevalence of patients having hypertriglyceridemia and increased CD25 levels accounted for respectively 65.6% and 87.5%, in the meantime, all patients had increased Ferritin and phagocytosis was seen in 95.8%. The most common cause of HLH was EBV infection accounting for 28.1%. The response rates after 2 weeks and 4 weeks were 7.3% and 21.9%, and the remission response rate after 8 weeks of treatment was 14.6%. The average of overall survival was 5.2 months. Conclusion: The study evaluating the outcome of the initial treatment of the HLH 2004 regimen showed that the remission rate after 8 weeks of treatment was low, while the mortality rate was high (62.5%). The mortality rate increases with age and increases in patients with triglyceride concentrations ≥ 3 mmol/L.